Re-imagining the divine in the world as she who changes - Christ, Carol P. (Mandrágora, 2025)
My work in feminism and religion has been shaped by the conviction that we-women men and ali living things-need the Goddess. I believe that the word "Goddess" can and must be spoken wherever feminists engage in re-imagining religion. ln their. most radical forms, feminist reimaginings of God as She and as Sophia and Shekhina in Jewish and Christian contexts have much in common with feminist re-i